(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Pathological changes in the oral cavity contribute to the development of various dental diseases. An increase in the incidence of periodontal diseases and dental caries lesions is the reason for the increased number of patients with diabetes mellitus seeking dental care. According to R. I. Runge (2014), 53.7% of patients with diabetes mellitus need orthopedic dental treatment. Dentures, even for patients without general somatic pathologies, have a number of side effects. Partially removable dentures have the greatest impact on the organs and tissues of the oral cavity. Impaired microcirculation of the tissues of the prosthetic bed, the function of salivation and factors of local immunity of the oral cavity contribute to the formation of dental plaque, which entails a change in the microflora of the oral cavity both quantitatively and qualitatively.